2019
DOI: 10.1161/circoutcomes.118.005429
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Recognition for Resuscitation Guideline Adherence and Rates of Survival for In-Hospital Cardiac Arrest

Abstract: Background: Hospitals participating in the national Get With The Guidelines (GWTG)-Resuscitation registry receive an award for high rates of adherence to quality metrics for inhospital cardiac arrest (IHCA). We sought to evaluate whether awards based on these quality metrics can be considered a proxy for performance on cardiac arrest survival.Methods and Results: Among 195 hospitals with continuous participation in GWTG-Resuscitation between 2012 and 2015, we identified 78 that received an award (gold or silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Ideal compliance with RECOVER guideline recommendations was variable for different BLS and ALS tasks in the current study. In human medicine, it has been well established, that the true benefit of practice guidelines can only be assessed against the background of guideline adherence and it has been shown that higher compliance with CPR guidelines leads to significantly higher quality of patient care, ROSC, and survival to hospital discharge rates (37)(38)(39). It therefore remains unclear what the benefit of the RECOVER guidelines for patient outcome would be if they were adhered to perfectly.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Ideal compliance with RECOVER guideline recommendations was variable for different BLS and ALS tasks in the current study. In human medicine, it has been well established, that the true benefit of practice guidelines can only be assessed against the background of guideline adherence and it has been shown that higher compliance with CPR guidelines leads to significantly higher quality of patient care, ROSC, and survival to hospital discharge rates (37)(38)(39). It therefore remains unclear what the benefit of the RECOVER guidelines for patient outcome would be if they were adhered to perfectly.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Our results support a broadened focus from intra-arrest variables to include other aspects of care and preventative measures that may affect outcomes following cardiac arrest, such as quality of resuscitation and post-resuscitation measures, team dynamics, communication, and leadership. 8,17 To the best of our knowledge, this study is one of the first looking exclusively at the ICU population and associations corresponding with that particular setting. One of the main strengths of this study is the size and time span of the investigation, with > 75,500 patients included over a time span of 13 years, providing detailed insight into the trends in quality metric adherence over time.…”
Section: Discussionmentioning
confidence: 99%
“…14 These metrics were derived based on a combination of AHA consensus statements, individual studies showing an association of these metrics with improved outcomes, and expert opinion. [15][16][17] They include time to epinephrine # 5 min, time to defibrillation # 2 min, and confirmation of airway device placement in trachea. 14 Prompt administration of epinephrine and defibrillation has been shown to be more likely to occur for IHCA in ICUs 18 ; however, few studies have specifically focused on the ICU population.…”
mentioning
confidence: 99%
“…Use of these metrics may explain why a previous study found no association between hospitals’ performance and their risk-standardized survival. 16 Thus, an incentive strategy focused on acute resuscitation care alone would be limited in reducing hospital variation in IHCA survival or increasing overall survival. Our study highlights the need to develop and validate hospital strategies that distinguish top-performing hospitals in postresuscitation care.…”
Section: Discussionmentioning
confidence: 99%